2016
DOI: 10.1038/srep38169
|View full text |Cite
|
Sign up to set email alerts
|

Efficient targeted mutagenesis of rice and tobacco genomes using Cpf1 from Francisella novicida

Abstract: CRISPR/Cas9 systems are nowadays applied extensively to effect genome editing in various organisms including plants. CRISPR from Prevotella and Francisella 1 (Cpf1) is a newly characterized RNA-guided endonuclease that has two distinct features as compared to Cas9. First, Cpf1 utilizes a thymidine-rich protospacer adjacent motif (PAM) while Cas9 prefers a guanidine-rich PAM. Cpf1 could be used as a sequence-specific nuclease to target AT-rich regions of a genome that Cas9 had difficulty accessing. Second, Cpf1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
201
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(215 citation statements)
references
References 53 publications
11
201
2
1
Order By: Relevance
“…We evaluated the parameters of transfection and single‐cell analysis by targeting mutations in the tobacco PDS gene ( NtPDS ). Tobacco ( N. tabacum ) is an amphidiploid derived from N. sylvestris and N. tomentosiformis (Endo et al ., ; Sierro et al ., ). Specific primers were designed to amplify PDS genes from the N .…”
Section: Resultsmentioning
confidence: 98%
“…We evaluated the parameters of transfection and single‐cell analysis by targeting mutations in the tobacco PDS gene ( NtPDS ). Tobacco ( N. tabacum ) is an amphidiploid derived from N. sylvestris and N. tomentosiformis (Endo et al ., ; Sierro et al ., ). Specific primers were designed to amplify PDS genes from the N .…”
Section: Resultsmentioning
confidence: 98%
“…In contrast to Cas9 which generates bluntended DSBs proximal to the PAM, Cas12a generates staggered DSBs distal from the PAM. In these studies it could be shown that via the CRISPR/Cas12a system targeted mutagenesis can be accomplished and that the appropriate mutations are heritable [72,73]. Similar to Cas9, only a subset of Cas12a orthologues shows robust activity in eukaryotic cells.…”
Section: Using Cas12a (Formerly Named Cpf1) In Plantsmentioning
confidence: 99%
“…In the last few years, researchers purposed several CRISPR‐Cas effector proteins that may have differences in experimental use and targeting specificity (Table ) . Interestingly, the possibility of RNA transcripts editing is valuable for treating genetic disorders.…”
Section: Crispr‐cas9—lots Of Choices For Gene Targetingmentioning
confidence: 99%